PECULIARITIES OF COMMERCIAL ACTIVITY IN MIXED COMBINED TRANSPORT - Lubiany, P. V.; Voitovych, O. A.; Kuzmenko, I. O. (Systems and Technologies, 2024)
The article examines topical issues related to commercial activities in the context of mixed combined transport and ways to improve the tariff system on the example of road and rail transport. One of the main ways to improve the tariff system is to differentiate it depending on the quality class of transportation and other transport services, as well as to gradually stop the practice of "cross-financing" and subsidising unprofitable activities at the expense of profitable ones. Today, the transport sector is able to meet only the basic needs of the population and the economy in terms of transportation volumes, but not in terms of quality. The current state of the transport sector does not fully meet the requirements for the effective implementation of Ukraine’s European integration course and the integration of the national transport network into the Trans-European Transport Network. To improve the efficiency and competitiveness of the transport sector, it is necessary to improve the legal mechanism for public- private partnerships, strengthen cooperation between the public and private sectors, state authorities and local governments, and implement the necessary reforms, including the introduction of decentralisation through coordinated public policy initiatives. This will create a solid foundation for the sustainable development of the transport sector and an open, competitive transport market. In accordance with the current legislation, the level of tariffs in transport is determined based on the standard costs per unit of transport work, profitability and tax liabilities. Settlements with consumers of public transport services are carried out in accordance with the current tariffs in accordance with the codes (charters) of certain types of transport, other legislative acts of Ukraine, as well as in accordance with international conventions to which Ukraine is a party and interstate agreements in the field of transport services. The authors propose a methodology for setting tariffs for mixed combined transportation based on an assessment of the efficiency of the entire transport system. Since mixed combined transport, in particular, containerised transport, combines the accuracy of road transport with costs similar to those of rail transport, the tariff for it should be in the range between the tariff for traditional rail transport and road transport.